BRAC RDP/RCP: annual financial review mission - Kellogg, Clifton G.; Pikholz, Lynn (Shorebank Corporation, 2016)
1. Executive summary 2. Management of savings and credit-related activities 3. Portfolio analysis 4. Branch profitability and RCP/BRAC Bank viability 5.Management responsibility